The climate of the ancient Near East. The Early Third Millenium BC in the northern Negev of Israel - Amiran, David H. K. (ERDKUNDE, 1991)
In the early third millennium BC there was only one city in the Negev that was not an oasis settlement, but still had a few thousand inhabitants. The area now has an annual rainfall of less than 200mm. The conditions that made the existence of an urban settlement possible at that time therefore require clarification. This thesis examines the precipitation fluctuations of this area in the present. On the plus side, normal rain-fed agriculture has been possible in at least the years in the last few decades. The assumption that such conditions prevailed almost regularly at the beginning of the third millennium, i.e. at the time of the Atlantic Optimum, would explain the existence of the ancient city of Arad. Extensive literature on the Near and Middle East proves that such an assumption is justified. The same sources also point to a pronounced and rather sudden aridization in the 27th century BC. BC, which could explain the end of the city of Arad.